Treatments of Thermal Neutron Scattering Data and Their Effect on Neutronics Calculations - Zu, Tiejun; Tang, Yongqiang; Huang, Zhanpeng; Qin, Shuai; Li, Jie; He, Qingming; Cao, Liangzhi; Wu, Hongchun (Frontiers in Energy Research, 2021)
In the conventional method to generate thermal scattering cross section of moderator materials, only one of the coherent elastic scattering and incoherent elastic scattering is considered in neutronics calculations. For the inelastic scattering, fixed incident energy grid is used in the nuclear data processing codes. The multi-point linearization method is used to refine the incident energy grid for inelastic scattering. We select ZrHx as an example to analyze the effects of the above described treatments on the reactivity of several TRIGA reactors. The numerical results show that the incident energy grid has obvious effect on the effective multiplication factor (keff) of the analyzed TRIGA reactors; simultaneously considering the coherent and incoherent elastic scattering also affects keff by tens of pcm.